The notion of actor in French semiotics: : from character to collective actor - Costa, Marcos Rogério Martins (2021)
The term actor emerges in the semiotic tradition to replace the concept of character (or dramatis persona). The aim of the article is to resume the theoretical assumptions of the aforementioned notion, bringing to light recent contributions. The theoretical foundation of this work is based, on the one hand, on the seminal studies of discursive semiotics (GREIMAS; COURTÉS, 2008; GREIMAS, 1973; 2014), and, on the other, on the recent developments of tensive semiotics (FONTANILLE; ZILBERBERG, 2001) . Methodologically, this study is intended to be descriptive (MARCONI; LAKATOS, 2003), making a non-exhaustive bibliographical review of the main theoretical assumptions related to the concept of actor and the construction of the concept of collective actor. As a result, the relevance of the concept addressed to contemporary discursive studies is verified, demonstrating the state of the art of the notion of actor in semiotic theory.